Role of Neutron Beam Applications in the Sustainable Socio-Economic Development of Pakistan - Shahzad, Khurram; Khan, M. Nasir (The Nucleus, 2024)
Pakistan Institute of Nuclear Science and Technology (PINSTECH) is the largest multidisciplinary research and development center in Pakistan. It has two research reactors namely PARR-1 and PARR-2. Neutron beam facilities have been installed only around PARR-1. It is a multipurpose research reactor that has been mostly utilized for the production of radioisotope and the training of scientists, engineers and technicians. The reactor is also utilized in the studies of neutron reaction cross-sections, nuclear structure, fission physics, radiation damage in crystals and semi-conductors, studies of geological, biological and environmental samples by neutron activation techniques, gemstone coloration, neutron radiography and neutron scattering. We have been investigating lattice dynamics, crystal and magnetic structure of materials and residual stress measurement using neutron scattering. In this manner, PARR-1 is effectively contributing to the socio-economic development of Pakistan.